Effect of integrated treatment on improving the enzymatic digestibility of poplar and the structural features of isolated hemicelluloses. (15th January 2021) - Sun, Shao-Chao; Sun, Dan; Wang, Han-Min; Li, Han-Yin; Cao, Xue-Fei; Sun, Shao-Ni; Yuan, Tong-Qi
Highlights: An integrated process was used to treat poplar to improve enzymatic digestibility. A maximum enzymatic hydrolysis efficiency of 96.1 % was achieved after pretreatment. 35.2–56.8 % of hemicelluloses were also obtained and well characterized. The dissolution of hemicelluloses was monitored by confocal Raman microscopy. Abstract: Herein, a two-step hydrothermal pretreatment combined with alkali extraction method was applied to deconstruct the poplar cell walls for enzymatic hydrolysis. Results revealed that 88.1 % of hemicelluloses and 77.6 % of lignin were removed during the integrated treatment performed at 180 °C and a maximum enzymatic hydrolysis efficiency of 96.1 % was achieved. Confocal Raman microscopy suggested that the removal of hemicelluloses from cell walls was inhomogeneous, and most hemicelluloses were released from the secondary wall. In addition, 35.2–56.8 % of hemicelluloses were isolated from the integrated treatment. Detailed structural analysis revealed that the water-soluble hemicelluloses possessed more branched structure than the alkali-soluble hemicelluloses and the hemicelluloses isolated from the poplar were mainly composed of a linear backbone of (1→4)- β -d -Xyl p with 4- O -Me- α -d-Glc p A attached as side chains. This work provides an efficient pathway to transform poplar into fermentable sugars and hemicelluloses with considerable yield.